Timeseries partitioning of ecosystem respiration components in seasonal, non-tropical forests; comparing literature derived coefficients with evaluation at two contrasting UK forest sites - McCalmont, Jon; Heinemeyer, Andreas; Morison, James; Xenakis, Georgios; Bell, Michael; Wilkinson, Matthew; Hastings, Astley (Frontiers in Forests and Global Change, 2024)
Introduction Understanding carbon flows within ecosystems is key to quantifying the impacts of land-use change in the climate. However, while the net exchange of CO2 between the ecosystem and atmosphere indicates global warming potentials, partitioning into individual flux components is needed to understand sinks and sources, residence times, and sensitivities to land-use impacts. Scaling from research site to region requires modelling evaluated against in situ measurements, but there is often a mismatch between outputs of process models (e.g., soil heterotrophic respiration (Rh)) and site-measured parameters (e.g., total soil surface respiration (Rs) or whole ecosystem respiration (Re)). Methods This study took a literature review approach to determine fractional coefficients for estimating Rh from Re or Rs and considered whether these fractions differed across a year in seasonal forests, where relative contributions of root respiration might be expected to vary between growing and dormant seasons. Compiled timeseries data were grouped by forest type (broadleaf, needleleaf, and mixed), and coefficients for a fraction of each component (Rs or Re) that Rh represented were calculated using two approaches, namely a simple annual mean value over all months and individual monthly means. These coefficients were then used to estimate Rh separately from higher-level fluxes (Re from eddy covariance and Rs from soil chambers), measured concurrently at two UK forest sites, and compared to Rh estimated from the same datasets using previously published generic coefficients as well as to concurrently measured Rh and Re. Results Both approaches resulted in much closer convergence of the two separate estimates of Rh (derived from Re or Rs) than previously published coefficients, particularly for Rh/Re coefficients that had previously been measured under peatland blanket bog rather than forest. Discussion/Conclusion This result suggests that land cover is an important factor in determining the relative contribution of heterotrophic respiration to higher-level fluxes and that the coefficients used would ideally be derived from studies on similar ecosystems.